Flow Visualization Study on the Effect of a Gurney Flap in a Low Reynolds Number Compressor Cascade - Roy Y. Myose and Jan-Christopher Lietsche and Dieter Scholz and Hartmut Zingel and Shigeo Hayashibara and Ismael Heron (AIAA, 2006)
The effect of a Gurney flap in a compressor cascade model at low Reynolds number was investigated using tuft flow visualization in a water table facility. Although small in scale, water tables have the advantage of low cost and the ease with which test conditions can be varied. In this experiment, tuft flow visualization was used to determine the outgoing flow angle for a NACA 65-(12)10 compressor cascade model with a solidity of 1.5 at a blade chord Reynolds number of 16,000. The baseline (no flap) results were found to be in good agreement compared to results in the literature for tests conducted at Reynolds number in the 250,000+ range. A second set of measurements were then taken for a Gurney flap with a height of 2% of the chord length attached to the trailing edge of the cascade blades. The results suggest that the Gurney flap energizes the flow and delays the stall at large incoming flow angles.
Keywords: Aeronautics; Aircraft Components and Structure; Aircraft Design; Aircraft Operations and Technologys; Aircraft Wing Components; Boundary Layers; Flow Regimes; Fluid Dynamics; Fluid Flow Properties; Fluid Mechanics; Hydraulic Pump; Hydraulics; Skin Friction; Vortex Dynamic; Adverse Pressure Gradient; Subsonic Compressors; Freestream Velocity; Gurney Flap; Flight Envelope; Gas Turbine Engines; Compressible Flow